2021
DOI: 10.1108/imds-10-2020-0603
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the risk at infractions: an ensemble comparison of machine learning approach

Abstract: PurposeThe infraction of securities regulations (ISRs) of listed firms in their day-to-day operations and management has become one of common problems. This paper proposed several machine learning approaches to forecast the risk at infractions of listed corporates to solve financial problems that are not effective and precise in supervision.Design/methodology/approachThe overall proposed research framework designed for forecasting the infractions (ISRs) include data collection and cleaning, feature engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In the monitoring of environmental pollutants PM2.5, the existing studies integrated EL with the satellite high-dimensional visualization method to realize the monitoring and prediction of pollutants [75,76]. Forecasting the risk in financial domain by an ensemble approach [77]. Driven by new technologies, new industries and new models, enterprises have increased investment in research and development in cutting-edge technologies and emerging fields.…”
Section: Application In M Categorymentioning
confidence: 99%
“…In the monitoring of environmental pollutants PM2.5, the existing studies integrated EL with the satellite high-dimensional visualization method to realize the monitoring and prediction of pollutants [75,76]. Forecasting the risk in financial domain by an ensemble approach [77]. Driven by new technologies, new industries and new models, enterprises have increased investment in research and development in cutting-edge technologies and emerging fields.…”
Section: Application In M Categorymentioning
confidence: 99%
“…Ensemble learning mainly involves training base classifiers and formulating combinations of base classifiers. The three most popular ensemble strategies are bagging, boosting, and stacking [8]. Therefore, in practical applications, both high-accuracy and diversified base classifiers are required for an effective ensemble model.…”
Section: Related Workmentioning
confidence: 99%
“…The logarithmic loss function is used in the classification problem, and (ft) represents the regularization term, which is used to control the complexity of the model, as shown in Eq. (8).…”
Section: Extreme Gradient Boosting (Xgboost)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [25], several supervised algorithms for prediction were compared to determine the best security control for each study case. A study [26] identified the most effective classification method for measuring regulatory violations. Additionally, AI is also incorporated into new methods.…”
Section: ) Risk Managementmentioning
confidence: 99%